Pengaruh Penambahan Abu Cangkang Kelapa Sawit Pada Tanah Lempung Paccinongang Kabupaten Gowa - Leonard Felix Widyo Sanderan; Irwan Lie Keng Wong; Monika Datu Mirring Palinggi (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Soil has an important role in a highway construction planning that serves to pass the load from the top layer, but not always the basic soil layer is able to function properly. Therefore, in this study was conducted to find out the effect of the addition of oil palm shell ash on clay soil to UCT (Unconfined Compression Test). The type of soil that will be usedfor penelitian is clay soil taken in Paccinongang area, Gowa Regency. The methodology in this study conducted several soil physical properties testing then Kompaksi testing to obtain optimum moisture content value, and Unconfined Compression Test to get strong press value (qu). The results of the study showed that the soil meets the physical properties of clay soil. From The Free Press Strong test on the ash content of the palm shell 0%, 3%, 6%, 9%, 12% and 15% at point 1 the free press strength value decreased from 0% by 0.362% and increased at 9% by 0.424%. Meanwhile, at point 2, it decreased by 0% by 0.445% and increased at 12% by 0.423%. From the Unconfined Compression Test on Paccinongang clay, Gowa Regency with the addition of oil palm shell ash from both samples, there was an increase in the addition of 9% and 12% of normal clay soil.